Educação e constituição do sujeito surdo : discursos que circulam na ANPEd no período de 1990 a 2010 - Barberena, Cinara Franco Rechico (Universidade do Vale do Rio dos Sinos, 2013)
This thesis aims at problematize how the discourses, spread in ANPEd from 1990 to 2010 have to establish truths that characterise pedagogical practices and constitute deaf students and subjects both in the school and in the Contemporary society. In order to do that, by operating with the concepts of discourse and normalization, and having the Foucauldian genealogy as inspiration, 57 works of two ANPEd Working Groups (WG) were analyzed: 54 works of the Special Education WG and three works of the Social Movements, Subjects and Educative Processes WG. This enabled the emergence of two analysis units, which have been regarded here as two intertwined movements for conducting the conduct of the deaf. The first movement takes the linguistic/cultural artifact as a pedagogical imperative in which language is seen as a possibility condition to guarantee learning, development, equality of opportunities, integration and insertion of the deaf in the deaf community, in the school, in the society and in the work market. In this sense, deaf students and subjects are not only produced to assume the centrality of the linguistic knowledge as a condition for their insertion in the school and in the society, but also incited to search for conducts and behaviors that make such centrality work. By fostering the circulation and permanence of deaf subjects both in the school and in the work market, this search is conditioned by deaf competences generated pedagogical practices by instituted by governmental policies, by knowledges instituted through specialists in the area, and by the very functioning of the school in the society. Hence, there is the second movement, which is related to the deaf competences. The school, as one of the main loci of subject production, by investing in the other, incites the subjects to increasingly invest in themselves; they take on competences to be inserted into the neoliberal game of participation and permanence in the work market, and become efficient subjects that generate profits. With such apparatuses, deaf subjects have been conducted both in the school and in the society, regarding the way that economically active subjects use the resources they have available, and the constitution of self-entrepreneur subjects, i.e. deaf subjects that are intent, creative, active and productive.
Keywords: Educação de surdos; Práticas pedagógicas; Normalização; Discursos; ANPEd; Deaf education; Pedagogical practices; Normalization; Discourses; ACCNPQ::Ciências Humanas::Educação